Nursing workload in intensive care unit: a mixed method study (Research, Society and Development, 2020)
This study aimed to analyze the nursing workload of an Intensive Care Unit. It is a mixed method study with a convergent parallel design. Quantitative data were collected using the Nursing Activities Scores in 73 patient records and submitted to descriptive and correlational analysis. Qualitative data were collected through interviews with 18 nursing workers and analyzed using the content analysis. Later, the quantitative and qualitative data were analyzed together, aiming at their integration. It was verified that patients occupy 70% of the time of a nursing worker, which indicates a high nursing workload. This result was confirmed by qualitative data, organized into the following categories: Care demand of ICU patients at a university hospital and Work organization: repercussions on nursing workload and patient safety, that evidenced a perception of high workload and problems in the work organization that even interfere with patient safety. Quantitative and qualitative data converged with each other and indicated that nursing workers are overloaded.